2018
DOI: 10.1002/jclp.22738
|View full text |Cite
|
Sign up to set email alerts
|

The role of therapist and patient in‐session behavior for treatment outcome in exposure‐based cognitive behavioral therapy for panic disorder with agoraphobia

Abstract: Objective: There is a very limited amount of research on the relationship between therapist and patient in-session behavior and treatment outcome in cognitive behavioral therapy (CBT) for panic disorder with agoraphobia (PD/AG).Additionally, the findings tend to be inconclusive. This study investigates the association between therapist competence, adherence, patient interpersonal behavior, and therapeutic alliance and outcome in a low-control CBT setting by using comprehensive measures.Methods: Twenty-six pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…With regard to the therapeutic alliance, our results suggest that it is not a significant predictor of symptom change in a one-session exposure treatment for SP. Our findings are in line with other studies on anxiety disorders that measured the therapeutic alliance and found no significant allianceoutcome relationship (e.g., Maiwald et al, 2019). It might be that the alliance is not equally important in the treatment of this diagnostic group as it is for other mental disorders.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the therapeutic alliance, our results suggest that it is not a significant predictor of symptom change in a one-session exposure treatment for SP. Our findings are in line with other studies on anxiety disorders that measured the therapeutic alliance and found no significant allianceoutcome relationship (e.g., Maiwald et al, 2019). It might be that the alliance is not equally important in the treatment of this diagnostic group as it is for other mental disorders.…”
Section: Discussionsupporting
confidence: 92%
“…An approach to these questions can be helped by recent findings that, although there are demonstrable differences between therapists in their levels of adherence, there are also sizeable differences within each therapist's caseload, as reported by Baldwin and Imel (2013), Boswell et al (2013), Imel et al (2011), andMaiwald et al (2019), for example. As these researchers have noted, the fact that therapists tend to vary in adherence across clients points to the mutual, interactive influence of the dyad on the therapist's choice of interventions, as the responsiveness model predicts.…”
Section: Considering the Issue Of Responsiveness In Specified Treatme...mentioning
confidence: 99%
“…With regard to the aforementioned clinical microskills, there are almost as many MLM studies that could not find a significant association between clinical microskills and treatment outcome (e.g., Bisseling et al, 2019; Boswell et al, 2013; Hogue et al, 2008; Huijbers et al, 2017; Maiwald et al, 2019; Southam-Gerow et al, 2021). Moreover, in a meta-analytic review, Webb et al (2010) demonstrated that the association between clinical microskills and outcome is quite small and not significantly different from zero.…”
mentioning
confidence: 99%